Technical rationality and the decentring of patients and care delivery: A critique of 'unavoidable' in the context of patient harm. Issue 2 (4th October 2017) - Hutchinson, Marie; Jackson, Debra; Wilson, Stacey
Abstract : In recent decades, debate on the quality and safety of healthcare has been dominated by a measure and manage administrative rationality. More recently, this rationality has been overlaid by ideas from human factors, ergonomics and systems engineering. Little critical attention has been given in the nursing literature to how risk of harm is understood and actioned, or how patients can be subjectified and marginalised through these discourses. The problem of assuring safety for particular patient groups, and the dominance of technical forms of rationality, has seen the word 'unavoidable' used in connection with intractable forms of patient harm. Employing pressure injury policy as an exemplar, and critically reviewing notions of risk and unavoidable harm, we problematise the concept of unavoidable patient harm, highlighting how this dominant safety rationality risks perverse and taken‐for‐granted assumptions about patients, care processes and the nature of risk and harm. In this orthodoxy, those who specify or measure risk are positioned as having more insight into the nature of risk, compared to those who simply experience risk. Driven almost exclusively as a technical and administrative pursuit, the patient safety agenda risks decentring the focus from patients and patient care.